Pemanfaatan Sabun Mandi Batang Ekstrak Kenikir (Cosmos caudatus) sebagai Repelen Aedes aegypti - Muhammad Husni Mubarok; Siti Hani Istiqomah; Abdul Hadi Kadarusno (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue viruses which is transmittedthrough Aedes aegypti mosquito bite. DHF is mainly found in tropic areas and often leads tooutbreak. One way to prevent this disease is using repellent. One of the ingredients that can beused as a natural repellent is the extract of kenikir (Cosmos caudatus). For ease use as repellent, the extract can be applied in soap bars. The objective of the study was to know the influence of soap bar with kenikir extract formulation on the repelling power for Aedes aegypti mosquitoes, and to know the most effective formulation, by conducting an experiment with pre-testpost-test with contol group design. The extract formulation used in this research was 9 ml, 11 ml,and 13 ml. The data were analyzed statistically by using one-way Anova and LSD (least signifycant different) tests, and the results show that the mosquito repelling powers obtained from various soap bar with extract kenikir formulation were significantly different (p-value = 0,008). Kenikir extracted soap bars which is meet the mosquito repellent standard were the first and thirdreplication of 13 formulation (i.e.100 % and 94 %, respectively) and the third replication of 100 mlformulation (100 %). To conclude, the most effective kenikir concentration is 13 ml.